Scale for Measuring Transformational Leadership in Public Sector Organizations in Sri Lanka: With Special Reference to Ministries of Western Provincial Council - Nilwala, N; Gunawardana, K; Fernando, R. L. S (International Journal of Management and Sustainability, 2017)
The most accepted Multifactor Leadership Questionnaire (MLQ) is heavily applied to measure the transformational leadership in private sector and central government organizations than provincial council organizations in Sri Lanka. Thus this paper describes the development of a 21 item instrument for assessing transformational leadership in provincial council organizations in Sri Lanka with special reference to the western provincial council. To do so, both qualitative and quantitative methods were applied in three fundamental stages recommended by Churchill (1979). Initially a qualitative research was undertaken in five ministries in the western provincial council within Colombo district through interviews with 15 senior and middle level administrative officers from different back grounds which produced 21 items with four factors emerged. These 21 -items were included in a questionnaire and quantitative study was undertaken with the same respondents who were currently involved in the service in the Western Provincial Council. 60 questionnaires were distributed and 56 questionnaires were returned and found to be useful 56, which represents a 93% response rate. More than half (52) of the respondents were female between the age of 40-55. To ensure the reliability and validity of the measures of transformational leadership construct, mainly reliability test, factor analysis, was used. Finally, 21 items were deducted into 10 items and a new scale was developed to measure the transformational leadership in public sector organizations with three dimensions idealized influence, inspirational motivation, intellectual stimulation and. Regarding the limitations of the study in this respect, only the senior and middle level managers were considered. The sample size was 60 and it was selected only from the western provincial council with the use of purposive sampling technique. Further studies with large sample size which covers the all provincial councils using newly developed scale to measure the transformational leadership and replication studies with other organizations would be useful for further generalizations of the newly developed scale.